2018
DOI: 10.1371/journal.pone.0193389
|View full text |Cite
|
Sign up to set email alerts
|

Time course of blast-induced injury in the rat auditory cortex

Abstract: Blast exposure is an increasingly significant health hazard and can have a range of debilitating effects, including auditory dysfunction and traumatic brain injury. To assist in the development of effective treatments, a greater understanding of the mechanisms of blast-induced auditory damage and dysfunction, especially in the central nervous system, is critical. To elucidate this area, we subjected rats to a unilateral blast exposure at 22 psi, measured their auditory brainstem responses (ABRs), and histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Since the auditory cortex is the most important brain region involved in auditory signal processing, the rapid cellular senescence in this brain region may have implications concerning the chronic auditory dysfunctions that are widely seen after blast exposures. Preclinical studies have shown acute and chronic neuronal degeneration in the auditory cortex after blast exposure (45). Electrophysiological evaluations of the auditory cortex after blast exposure showed spontaneous firing of neurons up to 3 months post-blast indicative of blastinduced tinnitus (46).…”
Section: Discussionmentioning
confidence: 99%
“…Since the auditory cortex is the most important brain region involved in auditory signal processing, the rapid cellular senescence in this brain region may have implications concerning the chronic auditory dysfunctions that are widely seen after blast exposures. Preclinical studies have shown acute and chronic neuronal degeneration in the auditory cortex after blast exposure (45). Electrophysiological evaluations of the auditory cortex after blast exposure showed spontaneous firing of neurons up to 3 months post-blast indicative of blastinduced tinnitus (46).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 140 7-day-old newborn mice, weighing 4.0 ± 0.5 g, were sham-operated ( n = 20) or modeled with IBI followed by transduction of lentiviral vectors carrying plasmids expressing miR-421 mimic alone or in combination with SC97 (4 μg/ml, Selleckchem, Houston, TX, United States), overexpression (oe)-PINK, or oe-PINK + oe-FOXO3, n = 20. The IBI model was established as previously described ( Ten et al, 2003 ; Kallakuri et al, 2018 ). Briefly, all mice were housed under controlled conditions of temperature (24°C), with free access to food.…”
Section: Methodsmentioning
confidence: 99%
“…On the right side, silver-stain densities for sham controls and single and repeated blast-exposed animals were 36.57 ± 6.09, 34.48 ± 5. 16…”
Section: Silver Staining In the Inferior Colliculusmentioning
confidence: 99%
“…Genomic analysis of the inner ear samples on days 1 and 28 post-blast exposures revealed differential expression of several genes involved in mechanotransduction, cytoskeletal reorganization, myelin development, and axon survival ( 9 ). Few preclinical studies have explored the acute and subacute changes in auditory signal processing centers in the brain after blast exposure ( 13 , 16 , 17 ). In the present study, we have evaluated the effect of single and repeated blasts on neuronal degeneration in the brain regions involved in auditory signal processing in rats to determine whether blast exposure can cause acute and chronic CASPD.…”
Section: Introductionmentioning
confidence: 99%